Perception of Youths Towards Farming as Means of Livelihood - C. Satapathy; S. Panda (Indian Journal of Extension Education, 2014)
The study was conducted covering six districts of the Odisha namely Khurda, Nayagarh, Kendrapada, Puri, Sambalpur and Jagatsinghpur with total sample size of 250. The sample was selected at random fulfilling the criteria of belonging to rural areas, below age group of 35 years, educated up to middle school standard and above, having experience in farming, in search of alternative job and experiencing dissatisfaction with farming.Mismatching of education of persons to work with soil and animals, hazards of climate, difficult to compete in the business, less remunerative character of farming and difficult to meet family requirements are the reasons for dislike of youths towards farming. Lack of farmers’ support policy, continuous land fragmentation, lack of facilities for agri- business, risk and hazards, lack of social security are the major constraints to retain youths in farming for livelihood. Strong marketing facilities, insurance policy, risk coverage, mechanized farming, regulatory technologies are the major expectations from govt. to take up farming. The suggestions for better farming enterprise in Odisha include export oriented farming, strong marketing facilities, strong production control system, farmer as friendly policy, infrastructure, irrigation and commodity group approach. However no farming less than 1 hect. of land is subject to debate as by the sample.